Application of the Role-Playing Game as a playful methodology in the construction of knowledge in microbiology in medical teaching (Research, Society and Development, 2020)
This study seeks to demonstrate through the experience report the importance of playfulness in the construction of knowledge, as well as in the acquisition and improvement of crucial skills in professional experience. This article is a qualitative descriptive study of the type of experience report developed by medical students at the Federal University of Delta do Parnaíba (UFDPar). The activities reported were developed in the discipline of microbiology, from the production of a playful teaching methodology for the review of one of the contents covered throughout the semester, for which the group decided to use the Role-Playing Game (RPG). The process of creating the teaching model was structured in three stages: idealization, preparation and presentation. The use of active methodologies becomes a fundamental device in the presentation of new content in classes taught. This stems from the ease of communication between different cognitive areas, which also help in the use and evolution of crucial skills in professional experience. Thus, the use of the methodology corroborated with other applications in teaching methods inside and outside the university, where the greater immersion of students, associated with the use of various areas of learning and teamwork, facilitates the acquisition of new forms of knowledge. and skills necessary for academic and professional life.